Analisis Tingkat Keterampilan Berpikir Kritis Siswa SMA - Susilawati, Endang; Agustinasari, Agustinasari; Samsudin, Achmad; Siahaan, Parsaoran (Jurnal Pendidikan Fisika dan Teknologi, 2020)
This aim of this research was to analyze studentsÃ¢â¬â¢critical thinking skills. The research was a quantitative descriptive research. The research of critical thinking skills was tested using essay questions. The instrument of critical thinking skills was developed based on EnnisÃ¢â¬â¢ critical thinking skill indicators, namely: identifying questions, proposing hypotheses, determining an action, considering the use of appropriate procedures, recording observation results, interpreting questions, identifying and dealing with irrelevance, and giving definitions. Based on the research result, 21% of students had medium critical thinking skills, 64% of students had low critical thinking skills, and 15% of students had very low critical thinking skills.